Comparison of the Optimum Barrier Properties of PET/PE and BOPP/CPP Laminate Structures - Suman Kumari (International Journal of Intelligent Systems and Applications in Engineering, 2024)
In this study the barrier properties of two different laminate structures are investigated which are typically used in food packaging industry: PET/PE (Polyethylene Terephthalate/Polyethylene) and BOPP/CPP (Biaxially Oriented Polypropylene/Cast Polypropylene). The objective of this was to check if a structure based on BOPP could serve as a feasible alternative to the standard and traditional PET-based structure, while offering potential similar advantages in terms of barrier requirements. For this Water Vapor Transmission Rate and Oxygen Transmission Rate were measured using MOCON PERMATRAN-W® Model 3/34 G and MOCON OX-TRON 2/21 respectively. As we know BOPP ( WVTR -1.5–5.9 g/m2/24hrs for 100µm film) has a good barrier to water vapor as compared to PET (WVTR - 3.9–17g/ m2/24hrs for 100µm film) and BOPP( OTR - 93–300 cc/m2/24hrs for 100µm film) has low gas barrier as compared to PET (OTR - 1.8–7.7 cc/m2/24hrs for 100µm film), thus a coating of EVOH (Ethylene-vinyl alcohol) is added to the BOPP film in order to improve the oxygen barrier properties of BOPP/CPP based laminate. The EVOH has polar hydroxyl groups present in vinyl alcohol which cause strong inter-and intramolecular bonding and which results in good gas barrier properties of EVOH. The final results of test performed on two laminates demonstrated that the BOPP/CPP laminate showed superior barrier properties compared to the PET/PE laminate which suggests that BOPP/CPP laminates can be used as an appropriate alternative to PET/PE structures for food packaging applications such as bakery items or snacks item. Further research could look into the suitability of each laminate structure for different food products based on the barrier requirements.